Malaysia’s Refugee and Asylum-Seeking Children: A Child Rights Perspective - Abdullah Khoso; Hanafi Hussin (Department of Government Studies Universitas Muhammadiyah Makassar, 2020)
This article has exhibited the child rights framework's relevance while assessing and analysing voiceless Malaysian refugee and asylum-seeking children's status. The secondary data has been segregated, themed and analysed under the child rights framework related to refugee and asylum-seeking children. The article argues that refugees and asylum-seeking children in Malaysia are treated as outsiders and threats to the social fabric; this rhetoric against refugees and asylum-seeking children has shaped Malaysia’s excluded legal and social treatment towards such children. It has also exacerbated the painful and excluded experiences of such children. The article also argues that only frameworks do not bring the desired results if the state constantly thrives on racialised politics. The analysis shows these children are subject to various social, economic, political, legal and normative issues, which have compelled them to live a quite stressful and challenging life. These children's difficult experiences show serious deficiencies and problems in the government structures and functions, which this article believes are the desired outcomes of Malaysia’s legal, political and social approach towards these children. The analysis also indicates that the UNCRC’s child protection systems and mechanisms (and the international community) are also unable to pursue the state to stop it making its independent choices in matters dealing with a vulnerable group of children and recognising them the rights holders rather as threats. The complexities and challenges in implementing such children’s rights also lie in the roles of the two separate mandate holders (i.e. UNHCR and UNICEF).